Multikultur dan Multiperspektif dalam HAM Internasional - Alkatiri, Zeffry (Wacana, Journal of the Humanities of Indonesia, 2006)
This paper discusses the problem of human rights in an international context in which it often causes conflict of interests among different nations. It turns out that the Human Rights Declaration does not always provide convenient guide to problem of human rights abuse. This paper aims at demonstrating differing views in the international discourse on human rights and the necessity to understand those differing views and issues related to human rights. This is crucial to avoid taking side unwisely.